Public international law : a practical approach / 2nd ed. - Hamid, Abdul Ghafur@Khin Maung Sein (Prentice Hall/ Pearson Malaysia, 2007)
The book provides a reasonably comprehensive introduction to public international law based on the modern practice of States, the practice of international organizations, and the decisions of international and national courts. It is a complete textbooks for students of public international law and also a must-read for students......